Dampak Revitalisasi Pasar Terhadap Pendapatan Pedagang DiPasar Sentral Kota Gorontalo - Hafid, Elvira Cahyani Putri; Dai, Sri Indriyani S.; Bumulo, Frahmawati (Pascasarjana STIE Amkop Makassar, 2025)
The results of this research show that 1). Market Revitalization has a positive and significant effect on Traders' Income in the central market of Gorontalo City. This means that every increase in Revitalization can increase Traders' Income in the Central Market of Gorontalo City. 2). Market revitalization has a positive and significant effect on people's shopping interest in the central market of Gorontalo City. This means that every increase in revitalization can increase people's shopping interest in the Central Market of Gorontalo City.Keyword: Market Revitalization, Traders' Income and Consumer Shopping Interest in Gorontalo City Central Market